Anti-Bacterial Activity of Procaine_4_ Hydroxycoumarin - Aqueous Copper Chloride: Aktivitas Anti-Bakteri dari Procaine_4_ Hydroxycoumarin - Tembaga Klorida Berair - Tadamoun Sabah Yuns; Zainab Alag Hasan; Abdulameer Abdullah Al-Musawi (Universitas Muhammadiyah Sidoarjo, 2024)
Background: The presence of a -N=N- double bond with two substituents, often aromatic rings, is what distinguishes azo compounds. Because of their exceptional qualities, azo dyes and their derivatives have become promising antibacterial substances. Materials and methods: The procaine_4_ hydroxycoumarin - aqueous copper chloride C9H6O3-C13H20N2O2 -CUCI2.H2O was prepared by many reactions, and tested as an antibacterial compound against (Pseudomonas aeruginosa, Staphylococcus sp., Proteus mirabilis, Shegilla sp, and Escherichia coli) according to the agar diffusion method. Results: The compound showed antibacterial activity against all bacterial isolates, two of which were resistant to antibiotics such as amikacin and amoxicillin. Conclusion: The ligand and its metal complex are known as biologically antibacterial Highlights: Azo compounds with aromatic rings exhibit promising antibacterial properties. Procaine_4_hydroxycoumarin-copper chloride tested via agar diffusion method. Effective against bacteria, including antibiotic-resistant strains like E. coli. Keywords: Anti-bacterial, Azo dye, procaine_4_ hydroxycoumarin- aqueous copper chloride